Fertility and obstetric outcomes after curettage versus expectant management in randomised and non-randomised women with an incomplete evacuation of the uterus after misoprostol treatment for miscarriage. (April 2017) - Lemmers, M.; Verschoor, M.A.C.; Overwater, K.; Bossuyt, P.M.; Hendriks, D.; Hemelaar, M.; Schutte, J.M.; Adriaanse, A.H.; Ankum, W.M.; Huirne, J.A.F; Mol, B.W.J.
Abstract: Objective: To assess fertility and obstetric outcomes in women treated with curettage or undergoing expectant management for an incomplete miscarriage after misoprostol treatment. Study Design: Between June 2012 and July 2014, we conducted a multicentre randomised clinical trial (RCT) with a parallel cohort study for non-randomised women, treated according to their preference. In the RCT 30 women were allocated curettage and 29 expectant management. In the cohort 197 women participated; 65 underwent curettage and 132 women underwent expectant management. Primary outcome was curation, defined as either an empty uterus on sonography at six weeks or an uneventful clinical follow-up. We used questionnaires to assess fertility and obstetric outcome of the first new pregnancy subsequent to study enrolment. Results: Curation was seen in 91/95 women treated with curettage (95.8%) versus 134/161 women managed expectantly (83.2%) (p = 0.003). The response rate was 211/255 (82%). In 198 women pursuing a new pregnancy, conception rates were 92% (67/73) in the curettage group versus 96% (120/125) in the expectant management group (OR 0.96, 95% CI 0.89;1.03, p = 0.34), with ongoing pregnancy rates of 87% (58/67) versus 78% (94/120), respectively (OR 1.12, 95% CI 0.99;1.28, p = 0.226). Preterm birth rates were 1/46 in the curettage group versus 8/81 in the expectant management group (OR 0.22, 95% CI 0.03;1.71 P = 0.15). Caesarean section rates were 23% and 24% for women in the curettage group and expectant management group respectively. Conclusion: In women with an incomplete evacuation of the uterus after misoprostol treatment, curettage and expectant management does not lead to different fertility and pregnancy outcomes, as compared to expectant management.